ANALISIS KEMAMPUAN DAYA SAING PT. DIRGANTARA INDONESIA GUNA MENDUKUNG SISTEM PERTAHANAN NEGARA - Adang Setia (Prima Center Indonesia, 2018)
The purpose of this master journal is to identify competitiveness PT. Dirgantara Indonesia (PTDI) to support the national defense system. This research is using the theory of reference are: (1) Five Forces Porter theory; (2) Design School Mintzberg theory; (3) Core Competence theory and Resource base strategy. PTDI is currently to the process of organizational transformation, the finding also suggest competitiveness can be said to be low. But there are a potential factors PTDI that lead to a competitive advantage in the industry. The researcher suggests that provide improve on the future development of the company PTDI and contribute to the realization of the national defense system.Keywords: Core Competency Theory, Design School Mintzberg Theory, Industrial Competitiveness, Porter’s Five Forces Theory, PTDI, Qualitative Research, and Resource-Based Strategy